O trabalho social da Igreja Metodista com imigrantes Bolivianos no bairro do Brás em São Paulo - Araujo, Luís Carlos Lima (2013)
The text examines the social project of the Methodist Church in the neighborhood of Brás with the Bolivian immigrants. Reviews the literature on the first movements of immigrants in Brazil, with the focus at the neighborhood of Brás, the Methodist Church and its project with Bolivian immigrants. The origin of this neighborhood, its importance and its historical relationship with the migratory movements are part of the reflections. The establishment of the church and its missionary characteristics are presented before a deeper study of the social project with Bolivians. Then, it reviews the relationship between the church and the American and European immigrants who came to Brazil in the late nineteenth century. Since 1980 is initiated the phenomenon of the growth of the Bolivian immigrant presence in the central neighborhoods of São Paulo, and as a result of this presence, for about ten years the Methodist Church has been developing a project to assist socially and religiously the sons and daughters of Bolivian immigrants. For the study of this issue was done a field research and interviews to the parties responsible for the project, a couple accompanying the project since its beginning; three pastors, one of them with Bolivian origins, and four young Bolivians who participate in the project. In research, were detected facts and relevant information for a critical analysis in of the prejudices, limitations in communication, limitations in cultural integration, lack of strategic planning and other bureaucratic aspects characteristic of the internal organization of the Methodist Church. The development of the urban context of the neighborhood of Brás, the demand for social assistance by the Bolivian immigrant population and the structural limits of the church appears as new challenges to the tradition and missionary practice of the Methodist Church.